2011
DOI: 10.1007/s10534-011-9465-y
|View full text |Cite
|
Sign up to set email alerts
|

Comparative antimicrobial activity and mechanism of action of bovine lactoferricin-derived synthetic peptides

Abstract: Lactoferricin B (LfcinB), a 25 residue peptide derived from the N-terminal of bovine lactoferrin (bLF), causes depolarization of the cytoplasmic membrane in susceptible bacteria. Its mechanism of action, however, still needs to be elucidated. In the present study, synthetic LfcinB (without a disulfide bridge) and LfcinB (C-C; with a disulfide bridge) as well as three derivatives with 15-, 11- and 9-residue peptides were prepared to investigate their antimicrobial nature and mechanisms. The antimicrobial proper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
39
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(45 citation statements)
references
References 31 publications
6
39
0
Order By: Relevance
“…No antagonism was observed between the antibacterial agents used and bLfcin against E. coli, S. aureus and P. aeruginosa. The MICs for the antibiotics markedly decreased when the peptide was added, as expected, indicating that bLfcin might act in combination with these antimicrobial agents against E. coli, S. aureus and P. aeruginosa [74].…”
Section: Synergy With Antibacterial and Anti-fungal Drugssupporting
confidence: 76%
See 3 more Smart Citations
“…No antagonism was observed between the antibacterial agents used and bLfcin against E. coli, S. aureus and P. aeruginosa. The MICs for the antibiotics markedly decreased when the peptide was added, as expected, indicating that bLfcin might act in combination with these antimicrobial agents against E. coli, S. aureus and P. aeruginosa [74].…”
Section: Synergy With Antibacterial and Anti-fungal Drugssupporting
confidence: 76%
“…Studies have indicated that bLfcin leads to depolarization of the cell membrane without causing the lysis of the cells [70], that it exerts its bactericidal effect initially by acting on the bacterial cell surface, and subsequently on the cytoplasmic contents [74].…”
Section: In Vitro Antibacterial and Anti-fungal Activitymentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, the possibility of an internal target for the action of these peptides against M. avium cannot be discarded. In fact, there are numerous evidences in the literature pointing to the probable existence of an internal target for lactoferricins (5,(47)(48)(49).…”
Section: Discussionmentioning
confidence: 99%